High-throughput sequencing reveals miRNA effects on the primary and secondary production properties in long-term subcultured Taxus cells - Zhang, Meng; Dong, Yanshan; Nie, Lin; Lu, Mingbo; Fu, Chunhua; Yu, Longjiang (Frontiers in Plant Science, 2015)
Plant-cell culture technology is a promising alternative for production of high-value secondary metabolites but is limited by the decreased metabolite production after long-term subculture. The goal of this study was to determine the effects of miRNAs on altered gene expression profiles during long-term subculture. Two Taxus cell lines, CA (subcultured for 10 years) and NA (subcultured for 6 months), were high-throughput sequenced at the mRNA and miRNA levels. A total of 265 known (78.87% of 336) and 221 novel (79.78% of 277) miRNAs were differentially expressed. Furthermore, 67.17% of the known differentially expressed (DE) miRNAs (178) and 60.63% of the novel DE-miRNAs (134) were upregulated in NA. A total of 275 inverse-related miRNA/mRNA modules were identified by target prediction analysis. Functional annotation of the targets revealed that the high-ranking miRNA targets were those implicated in primary metabolism and abiotic or biotic signal transduction. For example, various genes for starch metabolism and oxidative phosphorylation were inversely related to the miRNA levels, thereby indicating that miRNAs have important roles in these pathways. Interestingly, only a few genes for secondary metabolism were inversely related to miRNA, thereby indicating that factors other than miRNA are present in the regulatory system. Moreover, miR8154 and miR5298b were upregulated miRNAs that targeted a mass of DE genes. The overexpression of these miRNAs in CA increased the genes of taxol, phenylpropanoid, and flavonoid biosynthesis, thereby suggesting their function as crucial factors that regulate the entire metabolic network during long-term subculture. Our current studies indicated that a positive conversion of production properties from secondary metabolism to primary metabolism occurred in long-term subcultured cells. miRNAs are important regulators in the upregulation of primary metabolism.